The Effects of Preservatives on Antibiotic- and Preservative-Resistant Microbes and Nitrogen/Sulfur Cycle Associated Microbial Communities in Freshwater River Sediments - Chien-Sen Liao; Xuan-Di Cao; Wei-Chen Lee; Chu-Wen Yang (Antibiotics, 2023)
The intensive use of benzoic acid (BA), 4-hydroxybenzoic acid (HB), and dehydroacetate (DHA) as additives and preservatives in cosmetics and foods causes emerging environmental pollutions. Anthropogenic releases of BA, HB and DHA are primarily emissions into water and soil. However, few studies investigate the effects of BA, HB and DHA on microbial communities in freshwater river sediments. The aim of this study is to reveal the effects of BA, HB and DHA on microbial communities in freshwater river sediments. Tetracycline-, sulfamethoxazole- and preservative-resistant microbes were increased in the river sediments treated with BA, HB and DHA. The relative abundances of methanogen- and xenobiotic-degradation-associated microbial communities were also increased in the BA-, HB- and DHA-treated sediments. The relative abundance of four nitrogen cycle associated microbial groups (anammox, nitrogen fixation, denitrification, and dissimilatory nitrate reduction) were increased after the eighth week in the BA-, HB- and DHA-treated sediments. For the sulfur cycle, the relative abundance of thiosulfate oxidation associated microbial communities were increased after the eighth week in the BA-, HB- and DHA-treated sediments. Results of this study provide insight into the effects of BA, HB and DHA on antibiotic resistance, nitrogen cycle, sulfur cycle, drug resistance and methane production in freshwater aquatic environments.